Liberalization of international trade in services - Chane-Kune, Bernard (2000)
Opines services will be the key issue of the next round of multilateral trade negotiations, now that the ground work has been laid with the 1994 approval of the General Agreement on Trade in Services (GATS) and the few sectoral agreements agreed upon after that.